Solid Fuels From Algae Residues By Biomass Densification - LOO , MAN YEE (IRC, 2016)
As global attention focus more on algae for biodiesel productions, algae residues left behind makes the commercialization of algae oil extraction less appealing economically and its accumulation may pose threats to the living’s health and environment. Adding value to these wastes is the best solution, besides able to extend its lifespan value. The proposed method - algae residues (AR) are subjected to biomass densification, where it is pelletized and then tested for fuel properties analyses and physical attributes analyses.